The politics of colonial residential place names in Zvishavane, Zimbabwe: unmasking European hegemony - Charles Tembo; Tevedzerai Gijimah; Allan T. Maganga (Taylor and Francis Group, 2023)
The research is a qualitative analysis of the names that were given to residential places in Zvishavane during the colonial period. It seeks to examine the politics of naming through an analysis of toponyms of Shabbanie Mashava Mines residential areas in a bid to unmask European Hegemony. The research is inspired by nommo, a tenet of Afrocentricity through the use of discourse analysis and semi-structured interviews with the elderly members of Zvishavane community who were mine employees during the colonial period, the research recognises that colonial residential place names of the then Shabbanie mines show the dichotomies that existed between the white population and the black popula-tion. The names were meant to communicate colonial ideologies which were meant to place the African race at the periphery and the European race at the centre. The environment that produced toponyms around Zvishavane town reveals an insatiable appetite for the valorisation of European memory and privileges. The study concludes that naming is not a haphazard endeavor, but rather, a weapon that was used in the colonial period to lampoon and castigate the Black race. Through names, the paper exposes the nature of relations that existed between Blacks and Whites.